Instagram-Based Learning Media on The Subject Chemistry in Our Environment - Rengganis, Ajeng Ayu; Apriani, Nur; Sukemi, Sukemi; Kusumaningtyas, Pintaka (Universitas Negeri Gorontalo, 2025)
The appropriate use of learning media is essential as a tool to help students explore and enhance their understanding. In line with the advancement of time and technology, the learning process and access to information are no longer limited to what is provided by the teacher but can also be obtained from various sources, including social media. Therefore, this study aims to develop Instagram-based learning media as a self-learning resource for students. This media covers the topic “Chemistry in Our Environment”. The type of research used in this study is design and development based on the Richey and Klein model, which includes three stages: planning, production, and evaluation. This study resulted in the development of Instagram-based learning media on the subject Chemistry in Our Environment, which has been tested for its validity. The media contains learning outcomes, learning objectives, meaningful understanding, guiding questions, and learning materials presented on the Instagram account @belmiaclass. The validity test results indicate that this Instagram-based learning media is highly valid, with a score of 93% for content aspects and 100% for media aspects. Therefore, the media can proceed to the next stages, namely practicality testing and effectiveness testing.